Treatment performance and microbial community structure in an aerobic granular sludge sequencing batch reactor amended with diclofenac, erythromycin, and gemfibrozil - Bodle, Kylie B.; Mueller, Rebecca C.; Pernat, Madeline R.; Kirkland, Catherine M. (Frontiers in Microbiomes, 2023)
This study characterizes the effects of three commonly detected pharmaceuticals—diclofenac, erythromycin, and gemfibrozil—on aerobic granular sludge. Approximately 150 µg/L of each pharmaceutical was fed in the influent to a sequencing batch reactor for 80 days, and the performance of the test reactor was compared with that of a control reactor. Wastewater treatment efficacy in the test reactor dropped by approximately 30-40%, and ammonia oxidation was particularly inhibited. The relative abundance of active Rhodocyclaceae, Nitrosomonadaceae, and Nitrospiraceae families declined throughout exposure, likely explaining reductions in wastewater treatment performance. Pharmaceuticals were temporarily removed in the first 12 days of the test via both sorption and degradation; both removal processes declined sharply thereafter. This study demonstrates that aerobic granular sludge may successfully remove pharmaceuticals in the short term, but long-term tests are necessary to confirm if pharmaceutical removal is sustainable.